2006
DOI: 10.22136/est002006267
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico del consumo del calamar gigante en México y en Sonora

Abstract: El objetivo del trabajo es presentar un diagnóstico del consumo del calamar gigante en México y Sonora. Se realizó un análisis comparativo de las propiedades nutricionales y de los niveles de consumo del calamar gigante y los productos cárnicos. Para describir los aspectos relacionados con gustos y preferencias del consumidor del calamar gigante, se utilizaron resultados de 1,799 encuestas aplicadas en 14 ciudades del país. Los resultados de las encuestas indican que el consumo del calamar gigante, en frecuenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In Mexico and several Asiatic countries, jumbo squid ( Dosidicus gigas ) meat is highly consumed because has been considered as a good source of nutritive compounds such as vitamins (A, B, and D), poly‐unsaturated fatty acids, carbohydrates, essential and nonessential amino acids, minerals, and other important biomolecules (Luna Raya, Uriaga García, Salinas Zabala, Cisneros Mata, & Beltrán Morales, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico and several Asiatic countries, jumbo squid ( Dosidicus gigas ) meat is highly consumed because has been considered as a good source of nutritive compounds such as vitamins (A, B, and D), poly‐unsaturated fatty acids, carbohydrates, essential and nonessential amino acids, minerals, and other important biomolecules (Luna Raya, Uriaga García, Salinas Zabala, Cisneros Mata, & Beltrán Morales, ).…”
Section: Introductionmentioning
confidence: 99%
“…The giant squid (Dosidicus gigas) represents one of the most important fisheries in Mexico in terms of catch volumes. However, it is an underutilized and undervalued resource despite its abundance and its nutritional value [1]. In order to increase its value and promote its consumption, several researches have been carried out focused on obtaining protein concentrates from its mantle.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, one of the most successful strategies is promoting its consumption throughout the development of valueadded products. Recent evidence has shown that the consumption of squid value-added products has increased in the last years (Luna-Raya, Arag on Noriega, & Salinas-Zavala, 2009; Luna-Raya, Urciaga-García, Salinas-Zavala, Cisneros-Mata, & Beltr an- Morales, 2006).…”
Section: Introductionmentioning
confidence: 99%